Status of periodontal health in pregnant women after using a toothpaste with herbal extracts - Coronado Tamariz, Daniel Alvaro (2009)
The correlation between gum disease and pregnancy is highly proven. The aim of this study was to determine the status of periodontal health in pregnant women after using toothpaste with herbal extracts. 80 pregnant women of the Naval Medical Center “Cirujano Mayor Santiago Távara” participated in this prospective, longitudinal, quasi-experimental clinical study. The sample was divided in two groups, the experimental group received toothpaste with herbal extracts and the control group conventional toothpaste, both groups received a toothbrush. Data collected at baseline and after 28 days included severity of gingival inflammation, dental plaque and gingival bleeding. A significant reduction of periodontal disease was found in both groups, the experimental group had a better effect than control group. Differences between the groups were significant in gingival inflammation and dental plaque. The herbal toothpaste had a similar effect than conventional in the third trimester. The herbal toothpaste reduced periodontal disease in pregnant women without being consistently better than control. A certain reduction of herbal toothpaste’s effect in the third trimester is suggested.